Integrating video game research and practice in library and information science - Ratliff, Jacob A., 1983-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book brings together video gaming culture and its unique forms of communication with information behavior research while detailing the nuances of video games and their influence"--Provided by publisher.
A classification of video games and players -- Players as people -- Video game communication -- Video games and health -- Video games and society -- Video games and government -- Libraries and video games: why? -- Education and video games -- Libraries and video games: the practical -- Gaming and information behavior -- Gaming and user-centered design.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 04/18/2015).
Keywords: Libraries -- Special collections -- Video games; Video games -- Research; Video games -- Social aspects; Video games in education; Information behavior; Collection development; Education; Gaming spaces; Information seeking behavior; User centered design; User experience; Video game communication; Video game culture; Electronic books